Determinants of Intestinal Permeability in Healthy First-Degree Relatives of Individuals with Crohn's Disease. Issue 4 (April 2015) - Kevans, David; Turpin, Williams; Madsen, Karen; Meddings, Jon; Shestopaloff, Konstantin; Xu, Wei; Moreno-Hagelsieb, Gabriel; Griffiths, Anne; Silverberg, Mark S.; Paterson, Andrew; Croitoru, Kenneth
Abstract : Background: The Genetics, Environmental, Microbial Project is a multicenter study assessing etiological factors in Crohn's disease by studying healthy first-degree relatives (FDRs) of individuals affected by Crohn's disease. We aimed to evaluate the contribution of genetic, microbial, and environmental factors to the determination of intestinal permeability in healthy FDRs. Methods: IP was assessed using the lactulose-mannitol ratio (LacMan ratio). FDRs were genotyped for 167 inflammatory bowel disease-associated single nucleotide polymorphisms. Taxonomic profile of the fecal microbiota was determined by Illumina MiSeq pyrosequencing of 16S ribosomal RNA . The associations of LacMan ratio with demographic factors, inflammatory bowel disease-associated single nucleotide polymorphisms and the fecal microbiota were assessed. Results: One hundred ninety-six white FDRs were included. Eleven percent of FDRs had an elevated LacMan ratio (≥0.03). A multivariate analysis demonstrated that younger subjects and nonsmokers had higher LacMan ratios, P = 3.62 × 10 −4 and P = 0.03, respectively. The LacMan ratio was not significantly heritable, H2r, 0.13, P = 0.13. There was no association between any of the 167 inflammatory bowel disease-associated risk variants and LacMan ratio nor was there a correlation between fecal microbial composition and the LacMan ratio. Conclusions: We did not find LacMan ratio to be significantly heritable suggesting that the contribution of genetic factors to the determination of intestinal permeability in healthy FDRs is modest. Environmental factors, such as smoking, are likely more important determinants. The effect of age on intestinal barrier function has been underappreciated. Abstract : Article first published online 2 March 2015.Supplemental Digital Content is Available in the Text.